Searching the Medical Literatures through Internet: Review of MEDLINE Database - RAI, ARUN KUMAR (TULSSAA Journal, 2025)
This article gives some importent point of views concerning the databases available over Internet, further it shows how the medical professionals can make use of the online medical databases. It gives names of internet browsers and enumerates the most used search engines including the most used PubMed system. The article describes about the available versions of MEDLINE databases and search techniques in depth, i.e. types of available Search Field Suffixes. Finally it enlists some importent medical and paramedical databases. TULSSAA Vol.4(3) 2006 pp.7-13